Car Rental Contracts Establish Lessee Liability for Vehicle Damage: Kontrak Sewa Mobil Menetapkan Tanggung Jawab Penyewa atas Kerusakan Kendaraan - Achmad Adi Setiawan; Noor Fatimah Mediawati (Academia Open, 2025)
General Background: Lease agreements represent a common contractual relationship in civil law, regulating rights and obligations between property owners and lessees, including motor vehicle rental services that frequently generate legal disputes related to damaged rental assets. Specific Background: Disputes often arise when lessees refuse to assume responsibility for vehicle damage occurring during the rental period, creating financial losses and legal uncertainty for rental operators, as observed in a case study at Mas Joko car rental. Knowledge Gap: Limited legal scholarship examines practical implementation of lessee liability for rental vehicle damage through integrated normative and empirical analysis within Indonesian civil law practice. Aims: This study examines legal provisions governing lessee responsibility for vehicle damage under the Civil Code and explores legal settlement mechanisms available to rental owners when liability is denied. Results: Using normative legal research combined with empirical case analysis, findings indicate that under Civil Code provisions, particularly Articles 1548, 1560, 1239, and 1243, lessees bear legal responsibility for damage caused by negligence during the rental period unless proven as force majeure. Dispute resolution may proceed through non-litigation mechanisms such as negotiation, mediation, or arbitration, or through litigation procedures seeking compensation claims. Weak contractual documentation and insufficient evidence frequently hinder liability enforcement. Novelty: This research presents an integrated legal examination combining statutory analysis with real-world rental dispute practices through a structured case study approach. Implications: Strengthening written contract clauses, administrative documentation, and insurance utilization provides greater legal certainty and dispute prevention strategies for vehicle rental operations. Highlights: Statutory Provisions Assign Responsibility When Negligence During Rental Periods Is Proven. Alternative Dispute Resolution Offers Settlement Options Before Court Proceedings. Strong Written Agreements and Evidence Records Reduce Enforcement Obstacles. Keywords: Car Rental Contracts, Lessee Liability, Vehicle Damage Disputes, Civil Law Lease Agreements, Contract Breach Liability